AGROLANCE: REPRESENTATION OF GROWTH BALANCE OF TOMATO PLANTS IN DRY LAND IN THE CONTEXT OF A DANCE WORK - Desy Wulan Pita Sari Damanik; Alfassabiq Khairi (PT Inovasi Pratama Internasional, 2023)
Agrolance dance work is representation of research results entitled